2002
DOI: 10.1023/a:1021207031114
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Restricted semantic fields and resultant stimulus overselectivity are often thought to be typical of low-functioning autism, as is a strong visual processing preference. However, these conclusions may in part be an artifact of testing methodology. A 12-year-old, low-functioning and nonverbal autistic boy was tested on an auditory word-to-picture selection task. The picture foils were chosen to have visual features, semantic features, both, or neither in common with the correct answer. Errors were made more oft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…While the study [70] indicated the possibility of teaching autistic people to respond to the items of a compatibility stimulus, while [71] it was shown [72] that it is a rapacious stimulus (DSM-3: 1980). To define the disorder, this situation in a state in the studies that investigated in the previous period, while in the studies of the following studies, other apartments investigated other characteristics of the stimulus, which are the multiplicity of the stimulus, the distance between the items of the stimulus, the size and shape of the stimulus, and the study of [73][74][75][76][77][78][79][80][81][82] the correlation between family characteristics and food.…”
Section: Discussionmentioning
confidence: 99%
“…While the study [70] indicated the possibility of teaching autistic people to respond to the items of a compatibility stimulus, while [71] it was shown [72] that it is a rapacious stimulus (DSM-3: 1980). To define the disorder, this situation in a state in the studies that investigated in the previous period, while in the studies of the following studies, other apartments investigated other characteristics of the stimulus, which are the multiplicity of the stimulus, the distance between the items of the stimulus, the size and shape of the stimulus, and the study of [73][74][75][76][77][78][79][80][81][82] the correlation between family characteristics and food.…”
Section: Discussionmentioning
confidence: 99%
“…The behavioral comorbidities of ASD include aggressive behavior (up to 68%) [ 5 , 6 ] and repetitive self-injurious behavior (up to 50%) [ 7 , 8 ]. In children with ASD and self-injurious behaviors (SIB), over 75% of children will have persistence of these behaviors into adulthood, sometimes resulting in severe harm and even death [ 5 , 9 11 ]. SIB can be defined as repetitive “behavior which produces physical injury to the individual’s own body” with several different subclassifications [ 12 ].…”
Section: Introductionmentioning
confidence: 99%